2016
DOI: 10.1038/srep35855
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan inhibits CCL22 production through NF-κB pathway in M2 macrophages: a potential therapeutic strategy for cancer

Abstract: In tumor microenvironment, macrophages as a polarized M2 population promote tumor progression via releasing multiple cytokines and chemokines. A brown seaweed fucose-rich polysaccharide, fucoidan has antitumor activity and immune modulation through affecting tumor cells and lymphocytes. Here, we focused on the effect of fucoidan on macrophages especially M2 subtype. Our results demonstrated that fucoidan down-regulated partial cytokines and chemokines, especially a M2-type chemokine CCL22. Furthermore, fucoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 50 publications
(52 reference statements)
4
49
0
1
Order By: Relevance
“…This surface-activity of fucoidan is also reflected by the prediction of fucoidan effects on focal adhesion in the present study, which supports previous observations that low molecular weight fucoidan can attenuate aortic aneurism [15]. Additionally, research into fucoidan effects via MAPK cascade includes curative effects on leishmaniosis [18], affecting M2 type macrophages, inhibiting cancer growth by modulating immune responses [19], and reducing cerebral reperfusion injury [20]. Fucoidan interferes with the binding of cancer cells to extracellular matrix [34].…”
Section: Discussionsupporting
confidence: 91%
“…This surface-activity of fucoidan is also reflected by the prediction of fucoidan effects on focal adhesion in the present study, which supports previous observations that low molecular weight fucoidan can attenuate aortic aneurism [15]. Additionally, research into fucoidan effects via MAPK cascade includes curative effects on leishmaniosis [18], affecting M2 type macrophages, inhibiting cancer growth by modulating immune responses [19], and reducing cerebral reperfusion injury [20]. Fucoidan interferes with the binding of cancer cells to extracellular matrix [34].…”
Section: Discussionsupporting
confidence: 91%
“…Fucoidan also regulates immune responses that affect the production of chemokines and proinflammatory cytokines as well as the number and activity of immune cells [46][47][48][49]. For example, the expression of the M2-type chemokine CCL22 through the NF-κB pathway in M2 macrophages is downregulated by Fucoidan [50], which may inhibit tumor cell migration and regulatory T cell recruitment. These suggest that Fucoidan supplementation may alter cancer immunity that helps disease treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These results could be attributed to the TME acidity-increased positive surface charge via partial PDPA protonation to facilitate the cell uptake of nanodrug and the lysosomal acidity-triggered intracellular CUR release, which markedly increased the in vivo performance of CUR to inhibit the NF-B signaling pathway in tumor cells and TAMs. As CCL-22 has proved to modulate the tumor trafficking of T reg cells (8,22), the amounts of T reg cells (CD4 + Foxp3 + ) in tumor tissue of animals receiving different treatments were measured by flow cytometry. The CUR@PPC treatment significantly decreased the percentage of T reg cells in the tumor, as compared to the CUR-S treatment (3.6% versus 8.9%) or the PBS treatment (3.6% versus 16.7%) ( Fig.…”
Section: Tumor Infiltration Of T Cells Regulated By Nanodrugmentioning
confidence: 99%
“…Meanwhile, the CCL-22, a CC-chemokine subfamily member secreted by tumor cells and TAMs, may recruit the T reg cells to the tumor (7), which makes the suppression of CCL-22 secretion a potential means to reduce T reg cells in the tumor. Studies have shown that the expression levels of CCL-22, TGF-, and IL-10 are closely related to the nuclear factor  light-chain enhancer of activated B cells (NF-B) signaling pathway and the suppression of the NF-B pathway in cancer cells and TAMs may substantially inhibit the expressions of all these cytokines (8). Therefore, an NF-B pathway inhibitor is likely to reduce the tumor immune evasion, which can be expected to synergize with an immune checkpoint in-hibitor such as the anti-PD-1 antibody (aPD-1) to improve antitumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%